Persepsi Dosen Terhadap Gaya Berpakaian Mahasiswa (Studi Kasus Mahasiswa Fakultas Tarbiyah Dan Ilmu Keguruan Iain Kediri) - Surur, Agus Miftakus; Rozaq, M. F; Fikriyah, D.N (Happiness: Journal of Psychology and Islamic Science, 2020)
In FTIK, the students formed into educators, who are knowledgeable and insightful and have good character. Because an educator will be a role model for students. In FTIK, students should wear clothes that are more polite and more closed because FTIK students are prospective educators, so a reflection of being an educator must be accustomed to from now on. The researcher tried to get complete and in-depth information about the lecturers 'perceptions of the students' dress style of FTIK IAIN Kediri. So the researchers used this type of qualitative research. The perceptions of the lecturers regarding the style of dress according to the perceptions of the lecturers regarding the dress styles of the IAIN Kediri students, namely according to Islamic dress codes and also according to the IAIN Kediri regulations. Besides that, it can also differentiate FTIK students from other faculties with their dress styles.